Emotional social support and access to care among older people living with HIV in rural China. (6th February 2015) - Lin, Chunqing; Li, Li; Ji, Guoping; Jie, Wu
<x xml:space="preserve">Abstract</x> Objectives Globally, the number of older people living with HIV (PLH) is growing. Additionally, older PLH are facing particular challenges related to accessing health care. The objective of this study is to investigate the older PLH's access to care and its relationship to emotional and tangible social support. Methods A cross‐sectional study was conducted among 225 PLH who were 50 years of age or older in Anhui, China. A computer‐assisted personal interview was used to collect the participants' demographic characteristics, perceived health status, and access to care. The following two dimensions of social support were measured: emotional support and tangible support. The association between emotional/tangible support and access to care was calculated using Pearson's/point‐biserial correlations and with multiple linear regression. Results Higher tangible support was reported by the participants who were married or living with a partner, those who had higher annual income levels, and those with better perceived health status. Emotional support was correlated with higher education, higher income, and better perceived health status. Multiple regression analyses showed that access to care was significantly associated with emotional support (β = 0.2807, p < 0.0001) but not with tangible support (β = −0.0183, p = 0.7922). Conclusions The study findings point to the importance of providing emotional support for older PLH. It is suggested that emotional support should be provided for older PLH in addition to tangible assistance, in order to engage them in treatment and care. Copyright © 2015 John Wiley & Sons, Ltd.